Utilizing logs to identify complex lithology of tight marl reservoir in the Leikoupo Formation 32 Submember (T2l32) of the Sichuan Basin, China - Yuan, Rui; Wu, Zhiwei; Xin, Yongguang; Zhang, Hao; Wu, Saijun; Yang, Siyue (Frontiers in Earth Science, 2024)
Recent exploration has revealed that the Middle Triassic Leikoupo Formation 3 2 Submember (T2l3 2 ) in the Sichuan Basin contains unconventional marl reservoirs with significant natural gas potential. Due to limited cores, old wells, and conventional logs, however, the lithological understanding of T2l3 2 is incomplete and relies solely on inaccurate mud logs. This lack of lithological foundation challenges geology and petroleum research. To identify complex lithology, this paper presents a double-hierarchical workflow to identify seven types of lithology using logs. The first order distinguishes salt, anhydrite, and marl, while the second order further subdivides marl into anhydrite marl, argillaceous limestone, shaly limestone, and limy shale. Different rocks' logging response characteristics are summarized based on quantity-limited cores and micro-resistivity imaging logs. Lithological identification of 2D and 3D plots is established using sensitive GR, DEN, and RT. Corresponding identification standards are built in two hierarchies. According to these standards, the lithology of T2l3 2 is identified in a total of 119 wells. Finally, the lithological characteristics of vertical, horizontal, and plane are discussed in the research area. The research results may aid in comprehending the entire lithological characteristics of the complex marl reservoir in T2l3 2 of the Sichuan Basin. It would help the exploration potential of petroleum systems in turn.